PENGEMBANGAN E-MODUL PEMBELAJARAN BERBASIS KEARIFAN LOKAL PADA MATERI BANGUN DATAR KELAS 3 SDN 39 MATARAM - Rasta Cahyani Fadilah; Nurwahidah; I Nyoman Karma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the validity and practicality of local wisdom-based learning e-modules in class 3 flat building material. This e-module was developed as additionsl contsining local wisdom and is equipped with videos and quizzes. The research method used is R&D (Research and Development) with the ADDIE type development model used. Data on the validity and practicality of e-modules were obtained from questionnaire instrumentsin the form of media and material expert validation questionnaires, as well as student and educator response questionnaires. The results of the media validation data analysis were 84% and the material validation percentage was 78.58%, so the product was in the valid category. Data on the practicality percentage of e-module is 93,89% from the questionnaire responses from students and 82.5% from educators, so it is in the practical category. These results show that the local wisdom-based learning e-modue on class 3 flat building material developed is declared valid and practical to use.